Mekanisme Prinsip Syariah Pada Produk Bank Syariah - Abrori, Faizul (Lembaga Pusat Penelitian dan Pengabdian kepada Masyarakat (LP2M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
Indonesia is a country with a majority Muslim population, including a country where the growth of Islamic financial institutions is quite rapid. Internationally, Indonesia is seen as a strength and has great potential for global Islamic finance, according to the Islamic Finance Development Report 2014 Indonesia is in the Top 10 Islamic Finance Assets ( Million) ranks 9th with assets of 35,626. The mechanism of sharia principles in Islamic bank products is important to be studied comprehensively by him in this paper focused on: What is the meaning of Islamic bank? (2). What is the difference between Islamic banks and conventional banks? (3). How important is sharia principles in Islamic bank products? (4). What is the meaning of Profit Loss Sharing and its application in banking? (5). What is the meaning of Revenue Sharing and its application in banking? (6). How is the difference between Profit Loss Sharing and Revenue Sharing?. The theory of profit loss sharing was developed in two models, namely the mudharabah and musharaka models. The Mudharabah model refers to a form of business cooperation between two parties. The first party (shahibul maal) provides all the capital, while the other party becomes the fund manager (mudharib). Musyarakah model is a cooperation agreement between two or more parties to run a particular business. Each party contributes funds with an agreement that profits and risks are shared in accordance with the agreement. What is meant by revenue for a bank is the sum of the bank's interest income received from the distribution of funds or services on loans or deposits provided by the bank. Revenue in Islamic banking is the result received by the bank from the distribution of funds (investment) into productive assets, namely the placement of bank funds on other parties. This is the difference or number in excess of earning assets with bank receipts.